2023
DOI: 10.1093/narcan/zcad032
|View full text |Cite
|
Sign up to set email alerts
|

PKM2 dictates the poised chromatin state of PFKFB3 promoter to enhance breast cancer progression

Abstract: The hypoxic milieu is a critical modulator of aerobic glycolysis, yet the regulatory mechanisms between the key glycolytic enzymes in hypoxic cancer cells are largely unchartered. In particular, the M2 isoform of pyruvate kinase (PKM2), the rate-limiting enzyme of glycolysis, is known to confer adaptive advantages under hypoxia. Herein, we report that non-canonical PKM2 mediates HIF-1α and p300 enrichment at PFKFB3 hypoxia-responsive elements (HREs), causing its upregulation. Consequently, the absence of PKM2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…The culture media for all the cell lines was supplemented with 10% fetal bovine serum (FBS; Sigma, F7524), 100 units/ml of penicillin and streptomycin (Invitrogen, 15140122), and 2 mM/ l -glutamine (Invitrogen, 25030081). The Boris Binding Site mutant (BBS Mut) MCF7 and HCC1806 cell lines were generated as previously stated [ 30 , 31 ]. The media and cell culture conditions for CRISPR/Cas9 mutants were identical to the wild-type cells.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The culture media for all the cell lines was supplemented with 10% fetal bovine serum (FBS; Sigma, F7524), 100 units/ml of penicillin and streptomycin (Invitrogen, 15140122), and 2 mM/ l -glutamine (Invitrogen, 25030081). The Boris Binding Site mutant (BBS Mut) MCF7 and HCC1806 cell lines were generated as previously stated [ 30 , 31 ]. The media and cell culture conditions for CRISPR/Cas9 mutants were identical to the wild-type cells.…”
Section: Methodsmentioning
confidence: 99%
“…The PKM2 and PFKFB3 overexpression constructs were generated as previously mentioned [ 30 , 31 ]. Briefly, PKM2 was amplified using MCF7 cDNA as a template and cloned between Not I and Sal I sites of the plasmid pCMV-3tag-1a.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 14 ] Interestingly, studies have also demonstrated that PKM2 can regulate HIF-1α expression and activation. [ 12 , 15 17 ] Azoitei N et al [ 12 ] found that PKM2 entered the nucleus and activated NF-κB/p65 and HIF-1α in hypoxic pancreatic tumors, leading to increased transcription of vascular endothelial growth factors, ultimately triggering vascular endothelial growth factors-A secretion and angiogenesis. Liu WR et al [ 15 ] found that knocking down PKM2 in highly metastatic liver cancer cells HCCLM3 could reduce the expression of HIF-1α protein and the phosphorylation of AKT and JUK, while reducing liver cancer cell angiogenesis ability, reducing the number of tubules, number of tubules branching points, and tubule length.…”
Section: The Effect Of the Non-metabolic Enzyme Function Of Pkm2 In T...mentioning
confidence: 99%
“…Furthermore, recent research reported that the recruitment of HIF-1α and p300 mediated by nuclear PKM2 under hypoxia in breast cancer cells also caused the upregulation of 6-phosphofructo-2-kinase/fructose-2, 6-bisphosphatase 3 a glycolytic enzyme and positively associated with cancer progression and aggression). [ 17 ] These studies suggest that nuclear PKM2 can promote glycolysis by activating HIF-1α, potentially playing a role in various biological functions of HCC. These findings highlight the potential of PKM2/HIF-1α as a target for anti-HCC therapies.…”
Section: The Effect Of the Non-metabolic Enzyme Function Of Pkm2 In T...mentioning
confidence: 99%